2011
DOI: 10.1063/1.3639303
|View full text |Cite
|
Sign up to set email alerts
|

Local structure and paramagnetic properties of Zn1-xMnxO

Abstract: Having based on x-ray absorption spectroscopy, we point out structural phase separation in polycrystalline Zn1-xMnxO ceramics prepared by solid-state reaction. The samples are single phase in the wurtzite structure as x < 0.04. A Mn-concentration increase with x ≥ 0.04 results in the formation of a secondary phase of tetragonal ZnMn2O4 spinel. The feature of x-ray absorption spectra for the Mn K edge reveals an existence of Mn2+ and Mn3+ ions in Zn1-xMnxO, which are responsible for room-temperature para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…content increases, the E 2 (high) mode becomes very weak and broad. Such phenomena could be due to the broken symmetry induced by Mn dopants in the ZnO host lattice [10]. The Raman scattering results are well consistent with those of XRD.…”
Section: Raman Propertiessupporting
confidence: 84%
See 1 more Smart Citation
“…content increases, the E 2 (high) mode becomes very weak and broad. Such phenomena could be due to the broken symmetry induced by Mn dopants in the ZnO host lattice [10]. The Raman scattering results are well consistent with those of XRD.…”
Section: Raman Propertiessupporting
confidence: 84%
“…might be ferromagnetic with Curie temperature (T C ) above room temperature (RT) [2,3], ZnO-based diluted magnetic semiconductors (DMSs) are attracting much more attention. This has led to a large number of experimental [4][5][6][7][8][9][10] and theoretical [11,12] studies of TM-doped ZnO. Specially, among all the TMs, the doping of Mn in ZnO is most encouraging because the ionic radius of Mn 2+ is similar to Zn 2+ and the substitutional Mn 2+ has the highest magnetic moment.…”
Section: Introductionmentioning
confidence: 99%
“…4(a) and (b), M S of Zn 1−x Mn x O nanoparticles monotonously increases with increasing C Mn for x=0.08. However, Because ZnMn 2 O 4 appear in the Zn 0.9 Mn 0.1 O nanoparticles, the interaction between Mn 2+ and Mn 3+ ions within the ZnO matrix shows antiferromagnetism with anegative Curie-Weiss temperature[30] and the antiferromagnetic interaction suppresses ferromagnetic coupling of sample[31]. Thus, the M S value has resulted in Mn ion concentration, which can be attributed to the increase of oxygen vacancies in the samples…”
mentioning
confidence: 99%
“…For the samples with d > 72 nm, there is no lattice distortion around the Zn sites. The ε increase is thus ascribed to oxygen-related defects because the intensity of the peaks in the Fouriertransformed XAFS spectra is dependent on atoms surrounding the absorbing Mn atom [5]. It has been shown that oxygen loss occurs during themilling in an Ar ambient, leading to the presence of oxygen vacancies (V O ) [9].…”
Section: Resultsmentioning
confidence: 99%
“…Annealing at temperatures higher than 700 o C usually leads to the paramagnetic (PM) behavior because of the coexistence of Mn 2+ and Mn 3+ ions [5].…”
Section: Introductionmentioning
confidence: 99%